HORIZONTAL MERGERS AND INNOVATION‡. (20th September 2018) - Jullien, Bruno; Lefouili, Yassine
Abstract: This paper discusses the effects of horizontal mergers on innovation. We rely on the existing academic literature and our own research to present the various positive and negative effects of mergers on innovation. Our analysis shows that the overall impact of a merger on innovation may be either positive or negative and sheds light on the circumstances under which each of these scenarios is likely to arise. We derive a number of policy implications regarding the way innovation effects should be handled by competition authorities in merger control and highlight the differences with the analysis of price effects.